A scaffold cell seeding method driven by surface acoustic waves - Li, H.; Friend, J.R.; Yeo, L.Y.
Surface acoustic waves (SAW)have been employed to drive a particle suspension into a porous scaffold as a means for cell seeding. Straight, simple interdigital electrode structures were fabricated on lithium niobate to permit the generation of Rayleigh SAW radiation. Fluorescent microscopy was used to investigate the seeding process; the SAW-driven seeding process occurred in approximately 10 s, much quicker than if the scaffold were to be seeded by gravity-driven diffusional processes alone (430 min). Analysis of high-speed micrographic images demonstrated that the SAW method could also drive particles deeper into the scaffold, thereby significantly improving the uniformity of the particle distribution. The proposed SAW technique therefore offers a promising technology to dramatically improve the speed and uniformity of cell seeding in scaffolds, which might contribute to rapid and uniform tissue regeneration.
Keywords: SURFACE ACOUSTIC WAVE; TISSUE ENGINEERING; RAPID CELL SEEDING; MICROFLUIDIC ACTUATION